Exploring the Phytochemical Content and the Antioxidant Potential of Citrus Fruits Grown in Cyprus - Goulas, Vlasios; Manganaris, George A. (My University, 2012)
The physicochemical and phytochemical profile as well as the antioxidant properties of the most important Citrus fruits grown in Cyprus [orange (Citrus sinensis, cv. ‘Valencia’), grapefruit (Citrus paradisi, cvs. ‘White Marsh’, ‘Star Ruby’, ‘Rio Red’) and an interspecific hybrid (Citrus reticulata x Citrus sinensis, cv. ‘Mandora’)] were determined. ‘Valencia’ fruit exhibited the highest phenolic, flavonoid and ascorbic acid content, as well as a higher antioxidant potency, followed by ‘Mandora’ fruit and the three grapefruit cultivars. HPLC indicated significant diversity on flavanones among the examined fruits, while LC–MS analysis revealed the presence of hydroxycinnamic acid derivatives, polymethoxyflavones and a furocoumarin. Overall, this study provides supporting evidence for the superiority of ‘Valencia’ orange fruit as an excellent source of bioactive compounds. In addition, to the best of our knowledge, this is the first study thoroughly describing the phytochemical profile of ‘Mandora’ fruit, an interspecific hybrid cultivated in Cyprus.
Keywords: Antioxidant activity; Ascorbic acid; Carotenoid; Flavonoids; Grapefruit; Hesperidin; Mandora; Naringin; Orange; Phenolic compounds